Catalogue of knowledge and skills for sleep medicine - Penzel, T; Pevernagie, D; Dogas, Z; Grote, L; de Lacy, S; Rodenbeck, A; Bassetti, C; Berg, S; Cirignotta, F; d'Ortho, M; Garcia-Borreguero, D; Levy, P; et al. (Blackwell Publishing Ltd, 2014)
Summmary: Sleep medicine is evolving globally into a medical subspeciality in its own right, and in parallel, behavioural sleep medicine and sleep technology are expanding rapidly. Educational programmes are being implemented at different levels in many European countries. However, these programmes would benefit from a common, interdisciplinary curriculum. This 'catalogue of knowledge and skills' for sleep medicine is proposed, therefore, as a template for developing more standardized curricula across Europe. The Board and The Sleep Medicine Committee of the European Sleep Research Society (ESRS) have compiled the catalogue based on textbooks, standard of practice publications, systematic reviews and professional experience, validated subsequently by an online survey completed by 110 delegates specialized in sleep medicine from different European countries. The catalogue comprises 10 chapters covering physiology, pathology, diagnostic and treatment procedures to societal and organizational aspects of sleep medicine. Required levels of knowledge and skills are defined, as is a proposed workload of 60 points according to the European Credit Transfer System (ECTS). The catalogue is intended to be a basis for sleep medicine education, for sleep medicine courses and for sleep medicine examinations, serving not only physicians with a medical speciality degree, but also PhD and MSc health professionals such as clinical psychologists and scientists, technologists and nurses, all of whom may be involved professionally in sleep medicine. In the future, the catalogue will be revised in accordance with advances in the field of sleep medicine. Copyright © 2014 European Sleep Research Society 232 April 2014 10.1111/jsr.12095 Catalogue for sleep medicine Catalogue for sleep medicine © 2013 European Sleep Research Society.